Spinel-oxide-integrated BiVO₄ photoanodes with photothermal effect for efficient solar water oxidation - He, Bing (2022)
Spinel oxide materials have been widely used as oxygen evolution catalysts to enhance the photoelectrochemical (PEC) performance of photoelectrodes. Herein, we demonstrate that the water splitting efficiency of a photoanode can be further enhanced by introducing its photothermal effect. Under near-infrared radiation, the temperature of the NiCo2O4/BiVO4 photoanode increases moderately, leading to improved water oxidation kinetics and charge transport simultaneously. With the assistance of the photothermal effect, the obtained photoanode reaches a photocurrent density of 6.20 mA cm-2 at 1.23 V vs reversible hydrogen electrode. A series of spinel-type MCo2O4 oxides (M = Mn, Zn, Cu, and Fe) are deposited on the surface of the BiVO4 photoanode to show similar photothermally enhanced PEC performance. The research discovery provides a way for improving the catalytic activity of photoanode materials with a photothermal effect, which may be applied to various fields of energy conversion, including CO2 reduction, N2 fixation, and pollutant degradation.